2023
DOI: 10.1002/jmv.28607
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different vaccine platforms in reducing mortality and length of ICU stay in severe and critical cases of COVID‐19 in the Omicron variant era: A national cohort study in Iran

Abstract: Various severe acute respiratory syndrome coronavirus 2 vaccines with different platforms have been administered worldwide; however, their effectiveness in critical cases of COVID‐19 has remained a concern. In this national cohort study, 24 016 intensive care unit (ICU) coronavirus disease‐2019 (COVID‐19) admissions were included from January to April 2022. The mortality and length of ICU stay were compared between the vaccinated and unvaccinated patients. A total of 9428 (39.25%) patients were unvaccinated, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Furthermore, our results evidenced a shorter LoS for vaccinated patients compared to unvaccinated patients, suggesting a more rapid attenuation of severe symptoms, and providing insight for future research on an aspect that is still understudied and the subject of scientific debate [ 39 , 40 ]. Overall, this study contributes valuable information to the existing literature.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, our results evidenced a shorter LoS for vaccinated patients compared to unvaccinated patients, suggesting a more rapid attenuation of severe symptoms, and providing insight for future research on an aspect that is still understudied and the subject of scientific debate [ 39 , 40 ]. Overall, this study contributes valuable information to the existing literature.…”
Section: Discussionmentioning
confidence: 77%
“…This study has a significant advantage as most of the included patients experienced their first Omicron infection. By contrast, previous investigation 9 , 12 , 21 , 28 involved populations exposed to multiple waves of outbreaks, which could introduce biases in assessing vaccine efficacy due to previous viral infections and passive enhanced immune status.…”
Section: Discussionmentioning
confidence: 93%
“…Nonetheless, the case-control study design limited its level of evidence. Large-scale studies from Canada 21 and Iran 9 revealed an inverse dose-response relationship between vaccine dosage and in-hospital mortality but did not specifically examine the finding for inactivated vaccines. In contrast, a multi-center cohort investigation conducted in Spain and Argentina 12 has corroborated the efficacy of vaccines in mitigating in-hospital mortality among individuals afflicted with COVID-19 necessitating oxygen supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation